The power of elections - Erdmann, Gero (Development and cooperation, 2008)
Enhält Rezensionen von: Lindberg, Staffan I.: Democracy and elections in Africa. - Baltimore : John Hopkins Univ. Pr., 2006 + Nohlen, Dieter: Wahlrecht und Parteiensystem. - 5. Aufl. - Opladen : Budrich, 2007 + Votes, money and violence : politica parties and elections in Sub-Saharan Africa / publ. by Matthias Basedau ... - Uppsala : NAI / Scottsville, SA : Univ. of KwaZulu-Natal Pr., 2007